2013
DOI: 10.1080/13803395.2013.858661
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning in obstructive sleep apnea syndrome patients without comorbidities: Focus on the fractionation of executive functions

Abstract: OSAS without comorbidities did not lead to cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 61 publications
0
23
1
2
Order By: Relevance
“…In a review by Bucks et al (2013), five published articles were analyzed and disease severity was not associated with cognitive functions in three of them. Also, in another study by Borges et al (2013), no significant correlation was found between AHI and executive performance. These findings are also consistent with our study findings.…”
Section: Discussionmentioning
confidence: 82%
“…In a review by Bucks et al (2013), five published articles were analyzed and disease severity was not associated with cognitive functions in three of them. Also, in another study by Borges et al (2013), no significant correlation was found between AHI and executive performance. These findings are also consistent with our study findings.…”
Section: Discussionmentioning
confidence: 82%
“…Such inconsistent findings are a challenge for the field, and call in to question the proposed models of cognitive harm in OSA. These have led some authors to argue that OSA does not cause cognitive impairment, ipsum . Rather, they propose, the co‐morbidities commonly present in OSA such as hypertension, hyperlipidaemia, obesity with associated inflammation, diabetes or metabolic syndrome, are the primary causes of the neurological damage.…”
Section: The Role Of Co‐morbiditiesmentioning
confidence: 99%
“…Rather, they propose, the co‐morbidities commonly present in OSA such as hypertension, hyperlipidaemia, obesity with associated inflammation, diabetes or metabolic syndrome, are the primary causes of the neurological damage. In support of this view, one study that recruited individuals with OSA without co‐morbidities failed to find differences in cognitive performance between individuals with OSA and non‐OSA controls . Individuals with OSA without co‐morbidities, however, may not represent the norm in OSA, as increased co‐morbidity may itself be a consequence of the disorder, and vice versa .…”
Section: The Role Of Co‐morbiditiesmentioning
confidence: 99%
“…Dual-task performance-the ability to perform simultaneously two tasks that load on different storage domains-also constitutes a separable type of executive function (see Logie et al, 2004), as does planning, or the ability to organize behavior toward a specific goal that must be achieved through intermediate stages (Jurado and Rosselli, 2007;Oosterman et al, 2013), and the efficiency of access to long-term memory (see Fisk and Sharp, 2004). Updating, shifting and inhibiting are correlated but distinguishable abilities (see Miyake et al, 2000;Friedman and Miyake, 2004;Miyake and Friedman, 2012), and all six types of executive functions can be assessed separately in the same experimental setting (e.g., see Vaz et al, 2011;Ginani et al, 2011;Borges et al, 2013). Evaluation of one's own performance (metacognition) is also related to executive control (e.g., Fernandez-Duque et al, 2000) and has been little investigated in the caffeine literature.…”
Section: Introductionmentioning
confidence: 99%